Two mono- and dinuclear Ni(II) complexes constructed from quinazoline-type ligands: Synthesis, X-ray structures, spectroscopic, electrochemical, thermal, and antimicrobial studies. (7th July 2017) - Chai, Lan-Qin; Zhang, Kong-Yan; Tang, Li-Jian; Zhang, Jian-Yu; Zhang, Hong-Song
Graphical abstract: Two mono- and dinuclear Ni(II) complexes have been synthesized via complexation of Ni(II) acetate tetrahydrate withHL 1 andHL 2 . The spectroscopic data of two Ni(II) complexes were compared with the ligandsHL 1 andHL 2 . The differently geometric features of the obtained complexes1 and2 are observed by X-ray crystallography. In the crystal structure, complexes1 and2 form an infinite 1-D chain and2 into 2-D supramolecular frameworks. The electrochemical properties of1 and2 were also investigated by cyclic voltammetry. Moreover, thermal property of1 was also studied. In addition, the antimicrobial activity ofHL 1, HL 2, and complexes1 and2 were also investigated. Abstract: Two mono- and dinuclear Ni(II) complexes, [Ni(L 3 )2 ]·2H2 O (1 ) (HL 3 = 1-(2-[( E )-3-methoxy-2-hydroxybenzylidene]aminophenyl)ethanone oxime) and [Ni2 (L 4 )2 (CH3 COO)2 ] (2 ) (HL 4 = 1-(2-[( E )-2-hydroxybenzylidene]aminophenyl)ethanone oxime), have been synthesized via complexation of Ni(II) acetate tetrahydrate withHL 1 andHL 2 (HL 1 = 2-(2-hydroxy-3-methoxyphenyl)-4-methyl-1, 2-dihydroquinazoline 3-oxide, HL 2 = 2-(2-hydroxyphenyl)-4-methyl-1, 2-dihydroquinazoline 3-oxide) originally.HL 1, HL 2, and two Ni(II) complexes were characterized by IR, UV–Vis, and fluorescence spectroscopy, as well as by elemental analysis, respectively. The spectroscopic data of two Ni(II) complexes were compared with the ligandsHL 1 andHL 2 . The differently geometric features of the obtained complexes1 and2 are observed by X-ray crystallography. In the crystal structure, complexes1 and2 form an infinite 1-D chain and2 into 2-D supramolecular frameworks. The electrochemical properties of1 and2 were also investigated by cyclic voltammetry. Moreover, thermal property of1 was also studied. In addition, the antimicrobial activity ofHL 1, HL 2, and complexes1 and2 were also investigated.